Antidiabetic activity of leaves of Anthocephalus indicus A. Rich. in alloxan induced diabetic rats - Indu Umesh Sanadhya; Meeta Bhot; Jossy Varghese; Naresh Chandra (International Journal of Phytomedicine, 2012)
The present study aims to examine the antidiabetic potential of leaves of Anthocephalus indicus A. Rich. The aqueous extract of leaves was screened for serum glucose lowering activity. Diabetes was induced in Sprague Dawley adult male rats by intra peritoneal injection of alloxan monohydrate at 80mg/kg bw. to the rats. Aqueous leaves extract of Anthocephalus indicus A. Rich. at 400mg/kg bw was given orally to control and diabetic rats for 21 days. Blood samples taken from retro orbital plexus of rats were analysed for serum glucose level, total cholesterol, high density lipoprotein (HDL- cholesterol) and low density lipoprotein (LDL- cholesterol) as per standard kit method. The rats feed with aqueous leaves extract showed significant reduction in blood glucose, total cholesterol, triglycerides, HDL and LDL as compared to diabetic rats. Aqueous leaf extract results for antidiabetic activity were compared with standard drug glibenclamide at 10mg/kg bw. and the antidiabetic acitivity was found to be significant. Histopathological study of liver and pancreas of rats showed that alloxan caused damage in the liver cells and degeneration of pancreatic islet cells. Administration of aqueous leaves extract caused an improvement in damaged liver cells and degenerated pancreatic islet cells. Thus, Anthocephalus indicus can be considered as a good natural antidiabetic drug.